2022
DOI: 10.3390/ijms23052490
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Mesenchymal Stem Cells and Their Derivates for Osteochondral Regeneration

Abstract: Healing of articular cartilage defects presents a challenging issue, due to its regenerative shortcomings. Lacking vascularity and innervation of cartilage and low proliferative potential of chondrocytes are the main reasons for the limited healing potential of articular cartilage. Traditional reparative approaches are limited in their efficiency, hence there is a demand for novel reparative treatments. Mesenchymal stromal cells, preferred for clinical uses, can be readily derived from various sources and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Therapeutic strategies such as discectomy, microfracture, and autologous chondrocyte transplantation (ACT) alleviate the discomfort caused by disc degeneration and restore mobility, but these therapies do not regenerate the tissue architecture that mimics its native form (1). Therefore, mesenchymal stem cell (MSC) in regenerative medicine has emerged to reduce the chances of the degree of disease invasiveness and donor-side morbidity potentially resulting in superior regenerative potential (19,20). It is the best option with the huge chondrogenic potential and less hypertrophic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic strategies such as discectomy, microfracture, and autologous chondrocyte transplantation (ACT) alleviate the discomfort caused by disc degeneration and restore mobility, but these therapies do not regenerate the tissue architecture that mimics its native form (1). Therefore, mesenchymal stem cell (MSC) in regenerative medicine has emerged to reduce the chances of the degree of disease invasiveness and donor-side morbidity potentially resulting in superior regenerative potential (19,20). It is the best option with the huge chondrogenic potential and less hypertrophic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well demonstrated that there is a complex interplay among cells [T cells, B cells, plasma cells, mast cells, stromal cells, fibroblast-like synoviocytes (FLS), and macrophages], and soluble immune mediators are the major players in joint inflammation [ 11 ]. FLS, the main constituent cells in the synovium, maintain homeostasis in synovial tissue extracellular matrix and SF.…”
Section: Introductionmentioning
confidence: 99%